Association of Dyslipidemia and Obesity in Postmenopausal Bangladeshi Women (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Objectives: Menopause is a natural process. After menopause the morbidity and mortality from cardiovascular disease in women is increased due to lack of oestrogen protection, aging effect, increased body weight, android pattern of body fat distribution, changes in metabolism and lipid profile.1,2 So the present study is aimed at measuring the serum lipid profile and BMI in postmenopausal women of Bangladesh, thus detecting dyslipidemia and obesity to ascertain the relative risk of developing cardiovascular disease in this group.Methods: A cross-sectional study was conducted at the Obst and Gynae Department of Green life Medical College Hospital among 150 otherwise healthy postmenopausal women from October 2017 to April 2018. Fasting blood obtained for testing lipid profile. Serum total cholesterol, triglycerides and high-density lipoprotein (HDL) cholesterol were measured using enzymatic procedures. Low-density lipoprotein (LDL) cholesterol concentration was estimated by Friedewald formula. Questionnaire-cum interview method was used to obtain relevant informations. BMI was calculated from weight in kg and height in cm by Metric BMI calculator. Dyslipidemia was identified based on serum lipid levels following the standard protocol proposed by the national guidelines.Result: A total of 150 participants aged between 43 years to 70 years, were included in this study. Average age of the study subjects were 53.53±3.2 years. A mean duration of menopause was 7.23±0.92 years. The range BMI level was 19.1 to 36.6. Among them BMI 30. According to standard guideline BMI 30 (obese) normal lipid level was in 5.8% of the women, isolated hypertriglyceridemia found in 29.4% women and dyslipidaemia was in 64.8% women. HDL-C level was low in 83.3% women of >30 BMI group and normal in 66.67% women of normal BMI group.Conclusion: The prevalence of dyslipidemia, based primarily on the high cholesterol level and high LDL was observed among the overweight and obese group of study population. Therefore, it can be concluded that menopause leads to changes in lipid profile by increasing total and LDL cholesterol and by reducing HDL cholesterol which indicates menopause may be an additional risk factor for dyslipidemia causing cardiovascular disease in Bangladeshi women.Bangladesh J Obstet Gynaecol, 2020; Vol. 35(1): 20-24